Menulis Artikel Ilmiah untuk Meningkatkan Kreatifitas Menulis Guru MIS Al- Marwa - Nurlaili Nurlaili; Horia Siregar; Teguh Satria Amin (Departement of Mathematics Education, 2023)
The teacher is an educator who has knowledge in educating that can create generations to be more able to think logically and insightfully. However, the responsibility of being a teacher is very heavy, because you have to be more competent in your professional field. Writing scientific articles is one of the skills that must be possessed by a teacher. Where, writing cannot be separated from a teacher. The purpose of this study was to see how the process of increasing writing creativity was carried out by the teachers of MIS Al-Marwa. This research was conducted during workshop activities using the Classroom Action Research method which was carried out in two cycles (cycle I and cycle II). The data was taken by observing the activities of the Al-Marwa MIS teachers in workshop activities or workshop learning models with the aim of evaluating the teacher's creative abilities in writing articles. The analysis was carried out during the activities of the scientific article writing training workshop conducted by the MIS Al-Marwa teacher. From the results of the analysis carried out, there has been an increase in teacher writing creativity and this proves that the workshop learning model can improve teachers' ability to write scientific articles, where this model is rarely used by researchers.